LITERATURE REVIEW: EFEKTIVITAS MUSIK LATAR DALAM MENINGKATKAN KONSENTRASI BELAJAR MAHASISWA - Vigo Hantanto, Ken; Steven Hutabarat, Yusuf; Juanta, Palma; Wilfred Solo, Devin; Felicia, Felicia; Sebastian, Alvin; Gevira Sofa, Natasya (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This study aims to evaluate the effectiveness of background music in improving students' learning concentration through a literature review study. The results of previous studies show that background music can improve concentration. The first article used the Pretest Posttest Control Group Design method and found a significant difference with a calculated t value (3.100) greater than the t table (2.145). The fourth article used Quasi Experimental and Wilcoxon Signed Rank Test, showing a significant difference (p = 0.000). The seventh article, using qualitative methods, reported 83.3% of students agreed that music helps focus. However, the eighth article noted background music can improve mood but also increase cognitive load. In conclusion, background music, especially slow-tempo and instrumental, is effective in improving study concentration. Variations in effectiveness are due to music preference and learning context. Students and educators are advised to use background music that suits individual needs.